Sensitive-Spectrophotometric Determination of Methyl Dopa and Adrenaline - Afkhami, Abbas; Nouri-Zadeh, Akbar (Asian Journal of Chemistry, 2010)
A Simple, precise, sensitive and accurate method for determination of trace quantities of methyl dopa and adrenaline is described which is based on their reaction with Fe(III) in the presence of 1,10-phenanthroline at pH 5.4. There is a linear relation between the absorbance of produced ferroin at 510 nm and the concentration of methyl dopa and adrenaline in the rang of 0.01–0.8 μg ml–1, respectively. The relative standard deviation for ten determinations of 0.5 μg ml–1 of methyl dopa and adrenaline was 0.85 and 1.06% respectively. The 3σ limit of detection of the method was 0.009 and 0.017 for methyl dopa and adrenaline, respectively. The method was applied to the determination of methyl dopa and adrenaline in plasma and pharmaceutical preparations.